Nerve Conduction Studies in Type-II Diabetic Mellitus with and without Metformin Therapy & its Association with Vitamin B12 - Pokhrel, Suman; Thakur, Dilip; Limbu, Nirmala; Maskey, Robin; Lal Das, Binod Kumar (Annapurna Journal of Health Sciences, 2024)
Introduction: Type II Diabetes Mellitus (T2DM) is a heterogeneous group of metabolic disorders characterized by insulin resistance & and impaired insulin secretion. Metformin is a first line treatment oral hypoglycemic agent for patients with T2DM. Conversely, it has been found that the use of metformin is associated with malabsorption of vitamin B12, which may lead to more detrimental effects on peripheral nerves. Methods: A comparative cross-sectional study was conducted enrolling type II diabetic patients (Group A) with metformin therapy for more than 6 months (n=30), type II diabetics (Group B) without metformin exposure (n=11) and healthy controls (n=30). Nerve conduction study parameters of median, tibial, common peroneal & and sural nerves, serum glucose and serum vitamin B12 levels were measured. A way ANOVA (post hoc: Tukey) test was used to compare the variables using SPSS. 22.0. Results: T2DM with metformin therapy showed significantly longer latencies and lower amplitudes of both sensory and motor nerves when compared to healthy controls and T2DM without metformin therapy. NCS parameters showed more deleterious effects on the median, tibial and sural nerves of diabetic patients with metformin therapy. Diabetics undergoing metformin treatment had reduced vitamin B12 levels as compared to those without metformin therapy [194.03 (164.86-223.53) vs. 297.82 (258.99-363.00), p=0.001] and healthy controls [194.03 (164.86-223.53) vs. 287.50 (204.25-351.50), p=0.001]. Serum vitamin B12 level showed a strong negative correlation (significant at p<0.01 level) with duration of metformin exposure/ treatment in metformin-exposed diabetics. Conclusion: Long-term metformin therapy in diabetic patients is associated with significant vitamin B12 depletion, leading to alteration in motor and sensory NCS parameters. Thus, we recommend regular vitamin B12 screening and oral/ parenteral vitamin B12 supplementation to diabetic patients on metformin therapy.